Development of improved pertussis vaccine - Rumbo, Martin (Hum Vaccin Immunother, 2014)
Rates of infection with Bordetella pertussis, the gram-negative bacterium that causes the respiratory disease called whooping cough or pertussis, have not abated and 16 million cases with almost 200,000 deaths are estimated by the WHO to have occurred worldwide in 2008. Despite relatively high vaccination rates, the disease has come back in recent years to afflict people in numbers not seen since the pre-vaccine days. Indeed, pertussis is now recognized as a frequent infection not only in newborn and infants but also in adults. The disease symptoms also can be induced by the non-vaccine-preventable infection with the close species B. parapertussis for which an increasing number of cases have been reported. The epidemiologic situation and current knowledge of the limitations of pertussis vaccine point out the need to design improved vaccines. Several alternative approaches and their challenges are summarized.